The heterogenization of sulfanilic and sulfonic Acids and their catalytic activity in the liquidphase alkylation of phenol. - Ali, Tammar Hussein (2011)
The new mesoporous silica modified with sulfanilic and sulfonic acids was synthesized by using rice husk ash (RHA) as the silica source. The solid catalysts were denoted as RHABzSO3H and RHAPrSO3H. The as-synthesized solid catalysts showed good textural and structural properties.